2005
DOI: 10.1081/jdi-42724
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Proliferating Cell Nuclear Antigen in Lupus Nephritis (Class IV) and Membranoproliferative Glomerulonephritis

Abstract: It can be said that expression of PCNA on renal biopsy was correlated with activity indexes in LN. PCNA may be a prognostic indicator in MPGN and LN. However, apoptosis does not have a predictive value for MPGN and LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This study revealed that quantifying apoptosis in renal biopsies predicts relatively little regarding future renal function. This is in agreement with a recent study which found no predictive value of apoptosis for renal function in patients with lupus nephritis or membranoproliferative GN [13]. Further studies using dynamic remodeling with apoptosis and proliferation of renal cells during the course of such diseases may explain why the apoptosis rate at biopsy provides only a very narrow insight into these long-term processes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study revealed that quantifying apoptosis in renal biopsies predicts relatively little regarding future renal function. This is in agreement with a recent study which found no predictive value of apoptosis for renal function in patients with lupus nephritis or membranoproliferative GN [13]. Further studies using dynamic remodeling with apoptosis and proliferation of renal cells during the course of such diseases may explain why the apoptosis rate at biopsy provides only a very narrow insight into these long-term processes.…”
Section: Discussionsupporting
confidence: 77%
“…Some minor degree of apoptosis using detection of DNA fragmentation has been also described by other authors in apparently normal human kidney specimens [10]. Apoptosis of glomerular cells plays a role in IgA nephropathy and lupus nephritis, especially in the development of sclerotic glomeruli [10,11,12,13], but has been also reported in membranoproliferative GN, and FSGS [14, 15]. Savill [1] found that apoptosis is an important mechanism for the remodeling of glomeruli in proliferative GN in the anti-Thy 1.1 rat model, a model of reversible inflammatory proliferative GN.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach aimed at detecting nicks in DNA typical for apoptotic chromatin (the TUNEL reaction) has also been applied in lupus studies. The conclusion from these studies is not clear, because the TUNEL reaction has been reported to be positive in several forms of glomerulonephritis, including lupus nephritis (30,(34)(35)(36)(37)(38). The specificity of this method for apoptosis is believed to be rather low, because this reaction may be positive in necrotic, postmortem autolysed, reversibly damaged, or actively transcribed cellular DNA (39).…”
mentioning
confidence: 63%
“…Both kidney cell proliferation and apoptosis are possible mechanisms leading to chronic progressive renal histological changes in lupus nephritis [61,62]. Besides inducing proinflammatory cytokines and chemokines, in some studies TWEAK could also affect cell proliferation and survival [24,63].…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%